Exploring the nexus between healthcare tourism services and tourists' behavioural intentions in Penang: a comprehensive analysis / Nuraini Syakirah Shaharuddin ... [et al.] - Shaharuddin, Nuraini Syakirah; Abas, Siti Aisah; Mohamed Rani, Zaharah; Abd Halim, Norhazliza (2023)
Medical tourism has emerged as a focal point in the realm of global healthcare, generating heightened interest and competitive advantage within the medical industry worldwide. This trend aligns with the increasing focus on tourism development. Within this paradigm, the current qualitative study investigated the relationship between medical tour services and the behavioural intentions exhibited by tourists in Penang. Through semi-structured interviews with five tourists who sought medical tour services in Penang, this study uncovered a multifaceted landscape. The combination of factors from the fields of medical and tourism services shapes tourists' inclinations. The key factors include the affordability of pricing, the quality of medical services, and the promptness of service provision. Also, tourism service factors, including the attractiveness of tourist attractions, the suitability of accommodations to meet tourist needs, and the provision of well-being programmes, contributed to the increase in medical tourism in Penang. This study has significant implications for improving the service delivery of medical tourism and serves as a reference for future researchers. In conclusion, the study provides a perspective on the relationship between medical tour services and tourists' behavioural intentions, inviting further exploration into medical tourism in Malaysia.